PERAN BIDAN MEWUJUDKAN KESETARAAN GENDER DALAM PELAYANAN KB PADA PUS DI PRAKTIK MANDIRI BIDAN DIY - Wulandari, Amri (Universitas Jenderal Achmad Yani Yogyakarta, 2020)
Background: The number of male FP is only 1.81% (Kemenkes RI, 2014). Lacking public knowledge, awareness and concern for gender equality and justice, men are required to increase their participation in reproductive health and family planning. Objectives: The purpose of this study was to determine the role of midwives, inhibiting factors, how to overcome obstacles in realizing gender equality related to family planning services. Methods: Qualitative descriptive, sociological juridical approach, primary data types and secondary data, with qualitative analysis. Respondents 6 midwives PMB, 4 KB acceptors, accidental sampling. Results: In PMK No 1464, midwives play a role in providing counseling and counseling to married couples that not only women are required to use family planning but men need to use family planning. Good counseling and outreach to couples of childbearing age to provide an understanding of gender equality and contraceptive methods are expected to provide better results than without treatment. Conclusion:Based on the result of this research which had done showed that overcome obstacles must involve various sectors in realizing gender equality increasing access to health services, increasing promotion and counseling to increase knowledge and awareness of gender equality and justice issues.